Clinical spectrum of obstructed inguinal hernia and its clinical outcome - Shah, Rabin Pratap; Adhikari, Shashi Shekhar; Gautam, Khagendra (International Surgery Journal, 2024)
Background: Obstructed inguinal hernia is an emergency surgical condition the world over. The study was aimed to study the clinical spectrum of obstructed inguinal hernia and its management. Methods: This cross-sectional study was conducted at Department of General Surgery, Janaki Medical College and Teaching Hospital, Janakpur, Nepal. In this study, we included all cases, aged above 12 years, with obstructed inguinal hernia admitted in our department. Excluded cases were patients suffering from comorbid conditions predisposing to development of groin hernia and those who were unfit to undergo surgical intervention. Results: During the study duration, we included 60 consecutive patients fulfilling the study criteria. Mean age of the patients was 49.5±6.24 years, ranging from 12 to 78 years. The most common presenting symptoms were pain and irreducible swelling, observed in all patients. The onset of symptoms was less than 6 hours in 58% of the patients. The most common contents of the hernial sac was small intestine (47%). Herniorrhaphy was done in 73%. In our study, post-operatively there were wound infections in 5% cases, seroma in 4%, post-operative hematoma in 3% and paralytic ileus was present in one case. At 30 days post-operatively, one cases died (2%). Conclusions: Obstructed inguinal hernias continue to be a source of morbidity and mortality in Nepal. Wound infection rate was 6% and one case expired in the 30 day follow up period.